Quality of endoscopy reporting at index colonoscopy significantly impacts outcome of subsequent EMR in patients with > 20 mm colon polyps - Raju, Gottumukkala; Lum, Phillip; Ross, William; Thirumurthi, Selvi; Miller, Ethan; Lynch, Patrick; Lee, Jeffrey; Bhutani, Manoop S.; Shafi, Mehnaz A.; Weston, Brian; Blechacz, Boris; Chang, George J; Hagan, Katherine; Rashid, Asif; Davila, Marta; Stroehlein, John (Endoscopy International Open, 2019)
Background and study aims Endoscopic mucosal resection (EMR) is safe and cost-effective in management of patients with colon polyps. However, very little is known about the actions of the referring endoscopist following identification of these lesions at index colonoscopy, and the impact of those actions on the outcome of subsequent referral for EMR. The aim of this study was to identify practices at index colonoscopy that lead to failure of subsequent EMR. Patients and methods Two hundred and eighty-nine consecutive patients with biopsy-proven non-malignant colon polyps (> 20 mm) referred for EMR were analyzed to identify practices that could be improved from the time of identifying the lesion at index colonoscopy until completion of therapy. Results EMR was abandoned at colonoscopy at the EMR center in 71 of 289 patients (24.6 %). Reasons for abandoning EMR included diagnosis of invasive carcinoma (n = 9; 12.7 %), tethered lesions (n = 21; 29.6 %) from prior endoscopic interventions, and overly large (n = 22; 31 %) and inaccessible lesions (n = 17; 24 %) for complete and safe resection whose details were not recorded in the referring endoscopy report, or polyposis syndromes (n = 2; 2.8 %) that were not recognized. Conclusions In our practice, one in four EMR attempts were abandoned as a result of inadequate diagnosis or management by the referring endoscopist, which could be improved by education on optical diagnosis of polyps, comprehensive documentation of the procedure and avoidance of interventions that preclude resection.